2020
DOI: 10.1098/rspb.2020.1754
|View full text |Cite
|
Sign up to set email alerts
|

Stress in the city: meta-analysis indicates no overall evidence for stress in urban vertebrates

Abstract: As cities continue to grow it is increasingly important to understand the long-term responses of wildlife to urban environments. There have been increased efforts to determine whether urbanization imposes chronic stress on wild animals, but empirical evidence is mixed. Here, we conduct a meta-analysis to test whether there is, on average, a detrimental effect of urbanization based on baseline and stress-induced glucocorticoid levels of wild vertebrates. We found no effect of urbanization on glucocorticoid leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 100 publications
2
28
0
Order By: Relevance
“…The results of this study assessed effects of ALAN on two measures of physiological stress and contribute to an increasing body of evidence that the relationship between urbanization and CORT concentrations is complex and may vary depending on the species, city, age, sex, and time of the year ( Bonier 2012 ; Iglesias-Carrasco et al 2020 ). The results demonstrated that pCORT concentrations on day 13 of life were higher in forest than urban blue tit nestlings, but the concentrations of CORT in feathers were not significantly different between forest and urban populations (although the direction of the effect is the same).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study assessed effects of ALAN on two measures of physiological stress and contribute to an increasing body of evidence that the relationship between urbanization and CORT concentrations is complex and may vary depending on the species, city, age, sex, and time of the year ( Bonier 2012 ; Iglesias-Carrasco et al 2020 ). The results demonstrated that pCORT concentrations on day 13 of life were higher in forest than urban blue tit nestlings, but the concentrations of CORT in feathers were not significantly different between forest and urban populations (although the direction of the effect is the same).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are secreted by the adrenal gland after activation of the hypothalamic–pituitary–adrenal (HPA) axis and are considered to represent the allostatic demand on an animal ( Romero 2004 ; Crespi et al 2013 ; MacDougall-Shackleton et al 2019 ). Thereby, glucocorticoids have been widely used in urban ecological studies that have investigated effects of the urban environment on wildlife health and fitness ( Bonier 2012 ; Iglesias-Carrasco et al 2020 ). Urban life is often regarded as “stressful” for wild species, but an emerging body of evidence suggests that this may not always be true.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban areas are exposed to continuous stressful stimuli that are expected to alter CORT physiology. However, a recent meta-analysis has found no consistent differences between urban and rural birds (Iglesias-Carrasco et al 2020). Regarding noise pollution specifically, results are also contrasting.…”
Section: Introductionmentioning
confidence: 93%
“…Second, meta-analyses estimate the overall strength of evidence for a particular hypothesized effect by examining associations within many independent studies that have each addressed the hypothesis (e.g. effect of the environment on physiology and phenotype; Noble et al, 2018a;Gunderson and Stillman, 2015;Iglesias-Carrasco et al, 2020;Wu and Seebacher, 2020). Finally, qualitative comparative reviews of a research question provide synthesis of a topic and data, but do not present analyses of data (e.g.…”
Section: Introductionmentioning
confidence: 99%